Doping in Martial Arts: How Is It Managed? - Agung Nugroho; Arko Jatmiko Wicaksono; Hary Widodo; Santosa Budiharjo; Djoko Pekik Irianto; Rustamaji Rustamaji; Lismadiana Lismadiana (Journal of Coaching and Sports Science, 2025)
Background: Doping remains a persistent issue in martial arts, exacerbated by the easy access to over-the-counter medications containing banned substances. Despite existing regulations, athletes often lack comprehensive knowledge of anti-doping measures, leading to unintentional violations.Aims: This study aims to evaluate the effectiveness of a doping management program in improving knowledge and awareness of doping among martial arts athletes.Methods: A convergent parallel mixed-methods design was employed. Twenty-one national-level martial arts athletes were selected using purposive sampling. Data were collected through structured interviews and standardized questionnaires. The doping management intervention included a web-based doping screening tool, an anti-doping educational module, and a 24-hour online consultation clinic implemented during the 2024 National Sports Week (PON) training period.Results: Results showed a significant increase in athletes' knowledge of doping, with the mean score rising from 54% to 76% (p = 0.002), especially in terms of understanding Therapeutic Use Exemptions (TUEs). However, the study also found low utilization of online doping clinics, confusion regarding TUE procedures, and continued reliance on coaches for drug use. Document analysis and institutional mapping showed that coordination between stakeholders was fragmented, and socialization of anti-doping services was not optimal.Conclusion: The findings underscore that coaches play a pivotal role in doping management, serving as primary sources of information and guidance for athletes. Strengthening the involvement of coaches in anti-doping education is essential to maintaining a doping-free environment and ensuring the success of doping prevention strategies in martial arts.